The enhancers and barriers to the development of Malaysian lifelong learning communities: a case study in Shah Alam / Mohd Rashidee Alwi … [et.al.] - Alwi, Mohd Rashidee; Nasir Syed Mohamad, Syed Jamal Abdul; Said, Jamaliah; Haron, Shireen (2006)
This paper discusses the factors that facilitate and hinder communities in lifelong learning activities in Shah Alam city. Using qualitative approach 16 informants from various backgrounds were interviewed to identify the meaning of lifelong learning, learning opportunities, and enhancers and barriers to the development of lifelong learning in Shah Alam. The study found that lifelong learning was defined as a continuous learning process that included formal, non-formal and informal education. The informants also revealed that there were very wide learning opportunities provided by various parties in Shah Alam.